Manuscript Online Repository as Scholar References Source - Maknun, Moch Lukluil; Noviani, Nur Laili (The Sunan Ampel Review of Political and Social Sciences, 2023)
One of the alternatives to revive the religious manuscript researcher and scholar passion is by providing an easy online reference about religious manuscript. Some manuscript researcher of ex-Office of Religious Research and Development Ministry of Religious Affairs have started to make and maintain an online repository about religious manuscripts since 2019. The plentiful manuscript data, which is resulted from research, contain philological description aspect and digital photo file needs to be followed up more than just a research report or catalogue. It also needs to be easily accessible by other scholar and researcher in an open access repository. This online repository, managed by the researcher team, contain almost 450 religious manuscripts from Madura. The other data that will be uploaded are Islamic manuscript found in Bali, manuscript by K.H. Ahmad Rifa’i Kalisalak, Syaikh Mahfudz Termas, and also from K.H. Hasyim Asy’ari. Using descriptive qualitative method, this paper aims to answer and introduce to three aspects, namely: a) the importance of providing an open access of religious manuscript using online repository; b) the content and general description of religious manuscript online repository; and c) the guidelines on how to access and download the manuscript from online repository.